The Effect of Hand Fan Media on the Knowledge of Women of Reproductive Age Regarding Female Sterilization in the Working Area of Kayen Kidul Community Health Center, Kediri Regency - Naimatun Nur Hasanah; Herawati Mansur; Finta Isti Kundarti; Desy Dwi Cahyani (Jurnal Kebidanan Manna, 2026)
Introduction: Female Sterilization (MOW) is a long-term contraceptive method effective at preventing pregnancy; however, its utilization remains low due to a lack of knowledge among Women of Childbearing Age (WUS). Therefore, effective educational media are needed to improve WUS knowledge regarding MOW contraception. Research Objective: To determine the effect of hand fan media on the knowledge of Women of Childbearing Age regarding MOW contraception in the working area of ​​the Kayen Kidul Community Health Center, Kediri Regency. Methods: This study employed a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Pretest–Posttest Design. The population consisted of 62 WUS. The sample comprised an intervention group (31 respondents) and a control group (31 respondents), selected via cluster random sampling. The intervention group received a pretest and education using hand fan media over seven days, while the control group received a pretest and education via the lecture method. A posttest was conducted after seven days. Data analysis utilized Paired Samples t-Tests and Independent Samples t-Tests. Results: The Paired Samples t-Test showed a significant increase in knowledge in both the intervention group (7.74±2.04 to 9.16±1.86; p=0.000) and the control group (7.58±1.68 to 8.09±1.51; p=0.000). The Independent Samples t-Test yielded a p-value of 0.003 (p<0.05), indicating a significant difference in the knowledge improvement between the two groups. Discussion: The study results demonstrate that the increase in knowledge regarding Female Sterilization (MOW) contraception among Women of Childbearing Age (WUS) was greater in the group receiving education via hand fan media compared to the control group. Therefore, hand fan media can be recommended as an alternative educational tool in family planning services to enhance WUS knowledge regarding MOW contraception.